Pemberdayaan Kelompok Perempuan Penenun dalam Pengembangan Ekonomi Lokal dan Pelestarian Budaya - Riwu, Yonas Ferdinand; Bunga, Markus; Aman, Dominikus K. T; Sinlae, Yoan Tania; Djo, Rini Aryani (Universitas Muhammadiyah Mataram, 2025)
Abstract: Sabu weaving has its own attraction and has become an economic source for the Sabu community, especially women weavers. This service aims to empower women weavers so that they are able to adapt to the changing times, increase income and understanding in digital-based marketing, and maintain the preservation of Sabu weaving culture. The direct education and public assistance method involves involving the